Actual Ligation Frequencies in the Chromosome Conformation Capture Procedure - Gavrilov, Alexey A. (Public Library of Science, 2013)
Chromosome conformation capture (3C) and derivative experimental procedures are used to estimate the spatial proximity between different genomic elements, thus providing information about the 3D organization of genomic domains and whole genomes within the nucleus. All C-methods are based on the proximity ligation–the preferential ligation of joined DNA fragments obtained upon restriction enzyme digestion of in vivo cross-linked chromatin. Here, using the mouse beta-globin genes in erythroid cells as a model, we estimated the actual frequencies of ligation between the fragments bearing the promoter of the major beta-globin gene and its distant enhancers and showed that the number of ligation products produced does not exceed 1% of all fragments subjected to the ligation. Although this low yield of 3C ligation products may be explained entirely by technical issues, it may as well reflect a low frequency of interaction between DNA regulatory elements in vivo.